Pescoids and Chimeras to Probe Early Evo-Devo in the Fish Astyanax mexicanus - Torres-Paz, Jorge; Rétaux, Sylvie (Frontiers in Cell and Developmental Biology, 2021)
The fish species Astyanax mexicanus with its sighted and blind eco-morphotypes has become an original model to challenge vertebrate developmental evolution. Recently, we demonstrated that phenotypic evolution can be impacted by early developmental events starting from the production of oocytes in the fish ovaries. A. mexicanus offers an amenable model to test the influence of maternal determinants on cell fate decisions during early development, yet the mechanisms by which the information contained in the eggs is translated into specific developmental programs remain obscure due to the lack of specific tools in this emergent model. Here we describe methods for the generation of pescoids from yolkless-blastoderm explants to test the influence of embryonic and extraembryonic tissues on cell fate decisions, as well as the production of chimeric embryos obtained by intermorph cell transplantations to probe cell autonomous or non-autonomous processes. We show that Astyanax pescoids have the potential to recapitulate the main ontogenetic events observed in intact embryos, including the internalization of mesodermal progenitors and eye development, as followed with zic:GFP reporter lines. In addition, intermorph cell grafts resulted in proper integration of exogenous cells into the embryonic tissues, with lineages becoming more restricted from mid-blastula to gastrula. The implementation of these approaches in A. mexicanus will bring new light on the cascades of events, from the maternal pre-patterning of the early embryo to the evolution of brain regionalization.